Seasonal and Interannual Changes in Reproductive Parameters and Eggs Biochemical Composition of the Fishery Resource Pleuroncodes Monodon (Decapoda: Munididae) from the Humboldt Current System - Guzman-Rivas, F (Elsevier B.V., 2020)
Environmental variables are key drivers of reproductive traits in marine organisms, which can have significant economic consequences in commercial species. Pleuroncodes monodon is an important resource of the industrial fisheries’ fleet of the Humboldt Current System. This species is subject to seasonal variations in pivotal variables such as temperature and food availability, as well as, climatic events. We herein analyse the variations in reproductive parameters and in the eggs’ biochemical profiles in relation to environmental conditions. Differences in all studied parameters were found between 2014 and 2015. In 2015, fecundity (measured as total number of eggs) and protein content were higher than 2014, but lipid content showed the opposite pattern. Seasonal and interannual variations were also observed in the energy content per egg; whilst the brood energy content did not show seasonal or interannual variation. This information is of utmost importance for integrative management of this commercial good as the data measures dynamic variations in the species populations. Currently, this squat lobster is overexploit and so far, no seasonal nor interannual variations have been considered in its management plan. The present study provides evidences that the female lobsters need different management strategies to maintain sustainable fisheries of Concepcion, Chile. © 2019 Elsevier B.V.